Real Time Automatic Face Recognition System Using Lbph Technique - Jamett-Dominguez, M; Rojas-Flores, R (Institute of Electrical and Electronics Engineers Inc., 2021)
The aim of this paper is the development of a facial recognition system, implemented through software, using Python and OpenCV. Haarcascade and LBPH techniques are applied in the preprocessing, training, and recognition of faces from various databases and images obtained from a webcam. The main successful and unsuccessful results are presented, as well as the analysis of the training time for different amounts of images and organization in folders. © 2021 IEEE.